Leadership Strategies in Optimizing Facilities and Infrastructure to Enhance Education - Lael, Muhammad Zaenul (Proceeding International Conference on Religion, Science and Education, 2025)
The research ams to identify and analyze effective leadership strategies in optimizing school facilities and frastructure to improve the quality of education. The research problem raised is the role of leadership in muring that existing facilities and infrastructure in schools can be utilized optimally to support a quality learning process. This research uses a literature study (library research), where the object of this research is leadership strategies in optimizing facilities and infrastructure to improve the quality of education. This research uses data collection methods from journals/articles, textbooks, and periodicals. Data analysis is carried out by reading, coilecting, quoting, concluding, and interpreting the results obtained. The research results show that effective Iradership strateges in optimizing facilities and infrastructure include (mention research findings, for example: careful planning, active participation of all stakeholders, use of information technology, and regular maintenance of facilities). Consistent implementation of these strategies can improve the quality of learning and achieve Better educational goals.